Evidence of H10N8 influenza virus infection among swine in southern China and its infectivity and transmissibility in swine. Issue 1 (1st January 2020) - Fu, Xinliang; Huang, Yunmao; Fang, Bo; Liu, Yixing; Cai, Mengkai; Zhong, Ruting; Huang, Junming; Wenbao, Qi; Tian, Yunbo; Zhang, Guihong
ABSTRACT: Infection with a novel H10N8 influenza virus in humans was first described in China in December 2013, which raised concerns related to public health. This novel virus was subsequently confirmed to have originated from a live poultry market. However, whether this virus can infect other mammals remains unclear. In the present study, antibody specific for H10N8 influenza virus was detected in swine herds in southern China during serological monitoring for swine influenza virus. The pathogenicity and transmissibility of this H10N8 influenza virus to swine was examined. The results showed that swine are susceptible to infection with human-origin H10N8 influenza virus, which causes viral shedding, severe tissue lesions, and seroconversion, while infection with avian-origin H10N8 influenza virus causes only seroconversion and no viral shedding. Importantly, human-origin H10N8 influenza virus can inefficiently be transmitted between swine and cause seroconversion through direct contact. This study provides a new perspective regarding the ecology of H10N8 influenza virus and highlights the importance of epidemiological monitoring of the H10N8 influenza virus in different animal species, which will be helpful for preventing and controlling future infections by this virus.